O processo de reconstrução da identidade enunciativa do sujeito afásico no âmbito clínico público - Silva, Larissa Rizzon da (My University, 2017)
This research consists of the investigation of the process about the reconstruction of the enunciative identity of the aphasic individual in the public clinical scope. For this, it was analyzed the linguistic theories of Saussure (2002, 2012), Jakobson (2003) and Benveniste (2005, 2006), since they contribute significantly to the rehabilitative treatment of language disorders, such as aphasia. It was also evaluated, with regard to the aphasia disorder, its etiology, its types, the degree of severity, the standard tests and the procedures adopted by the Sistema Único de Saúde (Health Unic System), to proceed with the referral of the patient to evaluation and phonoaudiological rehabilitation. Finally, it was analyzed the phonoaudiological therapy sessions of an aphasic person, developed in the public clinical scope, based on the linguistic and aphasia studies as mentioned above. It was concluded that, due to the degree of severity, due to the procedures adopted by the Sistema Único de Saúde (Health Unic System) and other factors, the brain-injured individual will hardly reconstruct their enunciative identity in this interventive field (sic).
Esta pesquisa consiste na investigação do processo de reconstrução da identidade enunciativa do sujeito afásico no âmbito clínico público. Para isso, analisaram-se as teorias linguísticas de Saussure (2002, 2012), Benveniste (2005, 2006) e Jakobson (2003), dado que contribuem significativamente com o tratamento reabilitatório de distúrbios de linguagem, como a afasia. Averiguaram-se, também, no que concerne ao transtorno afasiológico, sua etiologia, seus tipos, o grau de severidade, os testes-padrão e os procedimentos adotados pelo Sistema único de Saúde, para proceder ao encaminhamento do paciente à avaliação e à reabilitação fonoaudiológica. Por fim, analisaram-se as sessões de terapia fonoaudiológica de um sujeito afásico, desenvolvidas no âmbito clínico público, com base nos estudos linguísticos e afasiológicos anteriormente citados. Concluiu-se que, devido ao grau de severidade, aos procedimentos adotados pelo Sistema Único de Saúde, e a outros fatores, o indivíduo cérebro-lesado, dificilmente, reconstruirá a sua identidade enunciativa nesse campo interventivo (sic).
Keywords: Sistema Único de Saúde (Brasil); Afasia; Identidade; Aphasia; Identity (Psychology)